Sinan: Tokoh Arkitek Genius Dawlah ’Uthmaniyyah - Mat Zain, Farid; Jamsari, Ezad Azraai (Jurnal Usuluddin, 2000)
Sinan was a military administrator and an architect during the Ottoman Empire. The purpose of this article is to highlight him as a prominent figure in Islamic Architecture. His work namely the Sehzade Mosque, the Suleymaniye Mosque and the Selimiye Mosque, are regarded as the epitome of unique Islamic architecture throughout history. His pioneering concept of "the organization of space and dome construction" had won him the title, ’the genius architect’ of the Ottoman Empire.